Variations in the nutritional status of school going children in four rural districts of Punjab, Pakistan - Mustafa, Faheem; Bacha, Umar; Munir, Mubbasher; Tanveer, Afifa; Tahir, Hafsa; Naseem, Mohsina; Khan, Rida; Afzal, Muhammad Naveed (Progress in Nutrition, 2021)
Childhood is a time when maximum growth in relation to physical, mental, emotional and psychological growth takes place. Diet and nutrition plays a key role for their health and wellbeing. Our main goal was to assess the nutritional status (prevalence of underweight, thinness, and stunting) in the school going children Punjab, Pakistan (district Layyah, Rajanpur, Okara and Bhawalnagar). This cross-sectional study was carried out from April to August 2016 on 399 children (48 female and 351 male) of ages between 9 and 16 years. Anthropometric measurements; weight, height, and age were taken in kilogram (Kg), centimeter (cm), and years correspondingly. According to the results, 23.1%, 17.5%, and 28.1% children were found to be underweight, slimness (thinness) and stunting. Moreover, 22.2% male children was found underweight, 30.8% stunted, and 13.7% was thin. Regarding the female participants 29.2% were underweight, 8.3% stunted, and 45.8% thinness, indicating stunting prevalence is more in male while underweight and thinness prevalence is more in female students. These results will be useful for policy makers while developing nutritional intervention programs.